2021
DOI: 10.3390/cancers13010121
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Physical Activity in Children and Adolescents with Cancer

Abstract: Background: to evaluate the safety and efficacy of a physical activity program (PAP) in children and adolescents with cancer. Methods: children and adolescents with cancer were randomly assigned in a 1:1 ratio to the six-month PAP (intervention group) or to the control group. The first evaluation was performed at the end of the PAP (T0 + 6 mo). At T0 + 6 mo, both groups received the six-month PAP with a second evaluation at T0 + 12 mo. The primary outcome was the evolution of exercise capacity measured using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…Although feasibility and safety have been described in the current literature ( 11 ), a concise evaluation of adverse events (AEs) occurring during exercise programs for children and adolescents with cancer is lacking. Interventional studies evaluating exercise interventions in childhood cancer patients and survivors mostly acknowledge no adverse events (AEs) ( 12 , 13 ). However, information about the evaluation of such AEs during interventional exercise studies is sparse, not recorded, or not published and no information is available about AEs occurring outside studies during exercise care programs.…”
Section: Introductionmentioning
confidence: 99%
“…Although feasibility and safety have been described in the current literature ( 11 ), a concise evaluation of adverse events (AEs) occurring during exercise programs for children and adolescents with cancer is lacking. Interventional studies evaluating exercise interventions in childhood cancer patients and survivors mostly acknowledge no adverse events (AEs) ( 12 , 13 ). However, information about the evaluation of such AEs during interventional exercise studies is sparse, not recorded, or not published and no information is available about AEs occurring outside studies during exercise care programs.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, three trials have been published in the last two years (2020 and 2021), evaluating the effects of a combined (muscle strength and aerobic exercise) training intervention in children and adolescents undergoing treatment for different types of cancer [ 44 , 45 , 46 ]. Nielsen et al applied a supervised in-hospital exercise intervention that included for the first time two healthy classmates chosen as ‘ambassadors’, with the aim of improving patients’ motivation for engaging in the exercise intervention [ 44 ].…”
Section: Exercise During Childhood Cancer Treatmentmentioning
confidence: 99%
“…The authors found a significant beneficial effect of exercise on leg (but not on arm) muscle strength, walking performance, fatigue, self-esteem, and self-reported physical function, although no benefits were found for anthropometric outcomes or for the remainder of the HRQoL domains [ 45 ]. In 2021, Saultier et al implemented a six-month exercise intervention including both in-hospital and outdoor activities [ 46 ]. The intervention induced improvements in CRF and HRQoL and these benefits remained six months later [ 46 ].…”
Section: Exercise During Childhood Cancer Treatmentmentioning
confidence: 99%
See 2 more Smart Citations